36th Winter School on Wave and Quantum Acoustics – Wisła, Poland, February 26 – March 02, 2007 - BUKOWSKI, Roman (Archives of Acoustics, 2007)
I have a great pleasure to inform the "Archives of Acoustics" Readers that the 36th Winter School on Wave and Quantum Acoustics, organized by Upper Silesian Division of the Polish Acoustical Society and Institute of Physics at Silesian University of Technology, is planned at February/March 2007 in beautiful scenery of Silesian Beskidy Mountains.As always, the School has been a place where achievements of various sections of acoustics (especially molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, acoustoelectronics, photoacoustics, acoustics of solids etc.) are being exchanged. Moreover, some similar and related topics, for example optoelectronics and thermal wave methods, will be presented too.As at previous two years the School will be divided on three different, but complementary, parts - Winter Workshops (WW). Chronologically it will be:3rd WW on Acoustoelectronics and Optoelectronics (chairman prof. Tadeusz Pustelny),3rd WW on Molecular and Quantum Acoustics (chairwoman dr Marzena Dzida), and12th WW on Photoacoustics and Thermal Waves Methods (chairman prof. Jerzy Bodzenta).After acceptation by revievers the School lectures will be published in one of two journals - in The European Physical Journal Special Topics (formerly Journal de Physique IV - Proceedings), which is published by EDP Sciences or in Journal of Molecular and Quantum Acoustics (annual journal published by Upper Silesian Division of the Polish Acoustical Society). Moreover, all Participants will obtain a last issue of the Journal of Molecular and Quantum Acoustics.Once again we have taken pains to organize this conference taking into account the fact that it is an important event for acousticians, opticians and other Polish and foreign scientists. We hope that this reach conference program will gain acceptance and respect among its potential participants. We count on your numerous response and active participation.